Commentary on the Judgment of the Provincial Audience of Barcelona of 21 November 2019 [notification of non-translated judicial document] [ECLI: ES: APB: 2019: 9450a] - Echebarría Fernández, Jonatan (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The commentary on the judgment of 21 November 2019 of the Provincial Audience of Barcelona on the appeal filed against the Order of 20 February 2019 analyses the need for translating judicial and extrajudicial documents delivered by the judicial authority of a European Union (EU) Member State to an addressee located in another EU Member State. The judgment sets out the views of the Spanish court by analysing relevant case-law of the Court of Justice of the European Union (CJEU) and agreeing with the most recent doctrine of the European court. However, the Spanish court cannot compel a court of another EU Member State to comply with Regulation 1393/2007.